Efeito da estimulação acústica por meio de próteses auditivas nos sintomas depressivos, desempenho cognitivo e qualidade de vida em idosos com perda auditiva - Ghiringhelli, Rosangela [UNIFESP] (2018)
Objective: To evaluate the effect of acoustic stimulation by hearing aids on depressive symptoms, cognitive performance and quality of life in the elderly. Method: This research was subdivided into two studies: longitudinal study, to evaluate the effect of acoustic amplification through hearing aids before and postfitting hearing aids; and crosssectional study to evaluate the effect of different acoustic stimulation times by means of hearing aids in the elderly. In the longitudinal study, 19 new elderly users of hearing aids were evaluated were evaluated. In the crosssectional study, three research groups were formed according to age and sex with 19 elderly people, according to the time of acoustic stimulation through hearing aids: GSEA group (without acoustic stimulation); G06M group (new users, with acoustic stimulation up to 6 months participants in the longitudinal study) and G18M group (users, with acoustic stimulation above 18 months). The elderly were classified according to the Brazilian Economic Classification (ABEP) and evaluated for the nonauditory aspects: depressive symptoms, by the geriatric depression scale (GDS15), cognitive processes, through the 10point Cognitive Screening (10CS), quality of life, by the Brazilian Version of the Quality of Life Questionnaire " Short Form Survey "(SF36), and regarding the auditory aspects: selfperceived difficulties of listening, by the "ClientOriented Scale of Improvement" scale (COSITM) and access to speech sounds through Speech Mapping. The G06M group received their hearing aids according to the Federal Government's National Policy on Auditory Health Care Brazil (SAS / MS No. 432, November 14, 2000). Nonlinear amplification digital hearing aids and prescription of gain and output values were calculated using the NAL / NL2 prescriptive method. These elderly patients were reassessed three to six months after the use of hearing aids. The elderly of the GSEA and G18M group were submitted to the research protocol only once. After data collection, they were submitted to statistical analysis with significance level of 5%. Results: In the longitudinal study, the result of the 10CS screening was significantly better after six months of AASI use (p = 0.003); there was no significant difference between the two moments of evaluation in the EDG15 and SF36 tests. In the significant difference between the GSEA and G06M groups (p=0.045). There was no association between the 10CS and EDG15 tests for the GSEA (p=0.063), G06M (p=0.421) and G18M (p=0.624) groups. The evaluation of the quality of life through the SF36 questionnaire showed that the domains General Health Status (p=0.024) and Pain (p=0.053) were significantly and marginally significant better the longer the acoustic stimulation time. In addition, there was a mean negative linear correlation between EDG15 and the General Health Status domains (p<0.0001). Conclusion: In the longitudinal study cognitive performance was better after six months of use of hearing aids. In the crosssectional study, it was observed a lower depressive symptomatology, better cognitive performance and better quality of life in the general health and pain domains in the elderly with a longer time of acoustic stimulation. There was a mean negative correlation between depressive symptoms and quality of life in both studies crosssectional study, the EDG15 test presented significantly better scores in the G18M group than in the GSEA group (p=0.026); in 10CS there was a statistically